Research for Practice: Crash Consistency: Keeping data safe in the presence of crashes is a fundamental problem. - ALAGAPPAN, RAMNATTHAN (Communications of the ACM, 2023)
This article discusses system crashes and how each level of the system needs to be implemented correctly and the system component interfaces need to be used correctly by applications in order to prevent crashes. Several papers are cited within this article exploring the file system, a lower level component within the system, an exploration of interface-level guarantees with bug-finders, crash-consistent programs, and how the newer concept of persistent memory interacts with system crashes.